Ethnobotanical survey of the ginger family in selected Malay villages in Peninsular Malaysia - Ibrahim, Halijah; Hean Chooi, Ong; Hassan, Rohani (Malaysian Journal of Science, 2000)
The study was carried out to document the traditional uses of plants belonging to the ginger family (Zingiberaceae) in 14 selected villages in the states of Kelantan, Selangor and Wilayah Persekutuan, Peninsular Malaysia. Sixteen species in 7 genera are used as food, medicine, spices, condiments, dyes and in rituals. Except Alpinia conchigera which can be found also in secondary forest, the species are cultivated in home-gardens. Only 3 of these species, i.e. Alpinia conchigera, Curcuma mangga and Etlingera elatior are native to Peninsular Malaysia.